Combined endovascular interventions for pulmonary embolism at high altitude in Tibet - Yang, Tengyan; Yang, Jian (Frontiers in Cardiovascular Medicine, 2024)
Background Managing pulmonary embolism (PE) at extremely high altitudes poses unique challenges due to harsh environmental conditions and limited healthcare resources. Method This study retrospectively analyzed Tibetan PE patients in the Tibet Autonomous Region of China to evaluate the effectiveness and safety of combined endovascular interventional therapy in high-altitude areas. Results The average altitude of long-term residence for Tibetan patients was 3,863.4 ± 317.4 m, with an average age of 62.0 ± 16.0 years, and the time from computed tomography pulmonary angiography (CTPA) diagnosis to interventional treatment averaged 2.8 ± 2.2 days. The operation time for these patients was 106.1 ± 22.2 min, and the intraoperative dose of alteplase used was 23.3 ± 5.0 mg. All 9 patients reported profound remission of dyspnea and chest pain after endovascular interventions. The heart rate (p < 0.05) and respiratory rate (p < 0.001) of all enrolled patients were significantly decreased, and the peripheral capillary oxygen saturation (SpO2) was significantly increased (p < 0.05) after interventions. No severe complications, such as bleeding, occurred in any patient. Conclusion This study demonstrated the potential clinical benefits and feasibility of combined endovascular interventional therapy for treating acute PE in extreme high-altitude regions.